Metode Prototype pada Sistem Informasi Manajemen Tugas Akhir Mahasiswa Berbasis Website - Arizal Arizal; Annisa Nurul Puteri; Furqan Zakiyabarsi; Dimas Febriyan Priambodo (STMIK Sinar Nusantara, 2022)
Final Project as a Research is one of the main requirements for the graduation of undergraduate students from universities. Supervisory guidance is one way to find solution for student research problems. The final project guidance process involves multiple parts: campus administration, supervisors, and students. However, this process is often difficult to carry out properly because of the busyness of each individual, both lecturers and students. As a result, the process for carrying out the final project was hindered. Another thing that makes the completion of the thesis slow is the administrative service procedure to complete the final project which is too time consuming. This research aims to simplify and speed up the process of completing the student's final project. The prototype method is used to develop the final project management information system. This information system is designed using use case diagrams, rich picture diagrams, and entity relation diagrams. Tests were carried out using the black box method. The result of the research is a final project management information system which makes the student's final project completion process more efficient and effective. This information system facilitates administrative services and monitoring of the final project because it is performed systematically and can be controlled in real time.